Food choices: concordance in Australian children aged 11–12 years and their parents. (4th July 2019) - Vivarini, Prudence; Kerr, Jessica A; Clifford, Susan A; Grobler, Anneke C; Jansen, Pauline W; Mensah, Fiona K; Baur, Louise A; Gibbons, Kay; Wake, Melissa
Abstract : Objectives: Snack foods—typically high in salt, sugar, fat and/or energy—are likely important to the obesity epidemic. In the context of a population-based health assessment involving parent–child dyads at child age 11–12 years, we report cross-generational concordance in intake at a controlled snack food observation. Design: Cross-sectional study (Child Health CheckPoint), nested within the Longitudinal Study of Australian Children. Setting: Assessment centres in seven Australian cities, February 2015–March 2016. Participants: Of all participating CheckPoint families (n=1874), 1299 children (50.3% girls) and 1274 parents (85.9% mothers) with snack data were included. Survey weights and methods were applied to account for the clustered multistage sample design. Outcome measures: Partway through the 3.5-hour assessment, parents and children attended Food Stop separately for a timed 15 min 'snack break'. One of four standardised box size/content combinations was randomly provided to all participants on any given day. Total food mass, energy, nutrients and sodium consumed was measured to the nearest 1 g. Pearson's correlation coefficients and adjusted multivariable linear regression models assessed parent–child concordance in each variable. Results: Children consumed less grams (151 g [SD 80] vs 165 g [SD 79]) but more energy (1393 kJ [SD 537] vs 1290 kJ [SD 658]) than parents. Parent–child concordance coefficients were small, ranging from 0.07 for sodium intake to 0.17 for carbohydrate intake. Compared with children with parents' energy intake on the 10th centile, children whose parents were on the 90th centile ate on average 227 kJ more. If extrapolated to one similar unsupervised snack on a daily basis, this equates to an additional 83 050 kJ per year, which could have a cumulative impact on additional body fat. Conclusions: Although modest at an individual level, this measured parent-child concordance in unsupervised daily snack situations could account for substantial annual population differences in energy, fat and sodium intake for children aged 11–12 years. Trial registration number: ISRCTN12538380 .